Wpływ podmiotów zależnych na efektywność funkcjonowania grupy kapitałowej (na przykładzie grupy kapitałowej KGHM Polska Miedź SA) - Sikacz, Hanna (The Influence of Its Subsidiaries on the Effective Functioning of the Polish Capital Group (on the Example of the Polish Capital Group KGHM Polska Miedź SA), 2005)
The paper presents the results of examination of the financial condition of the Polish Capital Group. The results are presented in the context of the function effectiveness of the dominant player and the Capital Group subsidiaries. The measurable effects of the KGHM Polska Miedź SA Capital Group were the subject of financial analysis referring to the 3-year period of its operation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 359-369